State Economic Policy and Reform in the Oil-exporting Countries on the Example of Saudi Arabia, the UAE and Iraq - Gukasyan, Gurgen Levonovich; Aifary, Abdel Kademovich; Semenovich, Valeriy Stepanovich; Mantsev, Vladimir Valerievich (International Journal of Economics and Financial Issues, 2016)
The study describes the role of state economic policy in the economic transformation of developing oil-exporting countries on the example of Saudi Arabia, the UAE and Iraq. The objective of the article is to show how state economic policy may be used for modernization of national economy. The study of state economic policy in Saudi Arabia, the UAE and Iraq used various methods of economic science. The method of systemic and economic analysis was used to analyze the economic situation and guidelines of state economic policy in Arab oil-exporting countries under review, illustrated in the scientific publications and official documents. The method of statistical analysis helps to systematize data and to comprehend the influence of state economic regulation and participation on the modernization of national economies. Many recommendations on the modernization of developing economies are concentrated on maximal limitation of state regulation of economy to release the market forces. Some publications recommend to use state regulation of economy and state participation in the developing countries more widely, than in the developed economies. The authors of the study identified specific experience and characteristics of state regulation of economy and state participation in the developing economies on the example of oil-exporting countries such as Saudi Arabia, the UAE and Iraq. The authors of the study believe that some characteristics of state regulation of economy in Saudi Arabia, the UAE and Iraq may ensure a real progress in economic modernization and must be used in future as efficient. The study can contribute to understanding the paradigm of relationship between state regulation of economy and market environment in developing countries and to promotion of investigations in economic policy for transitional economies. Keywords: state economic policy, global oil market, state regulation of economy, economic infrastructure, financial crisis. JEL Classifications: G18, O10, O13